Deep learning for numerical solutions of Hesegawa-Wakatani system. - He, Yutian (Nanyang Technological University, 2024)
In this paper， we use high-order splitting method to discretize the scheme of 2D-Hesegawa-Wakatani system ，generate numerical solutions of this system by BOUT++ and use DNN neural network to train a model from row-zonally average electrical density and vorticity to its local flux.